Effector Functions of Natural Killer Cell Subsets in the Control of Hematological Malignancies - Gismondi, Angela; Stabile, Helena; Nisti, Paolo; Santoni, Angela (Frontiers in Immunology, 2015)
Treatment of haematological malignant disorders has been improved over the last years, but high relapse rate mainly attributable to the presence of minimal residual disease still persists. Therefore, it is of great interest to explore novel therapeutic strategies to obtain long-term remission. Immune effector cells and especially NK cells play a crucial role in the control of haematological malignancies. In this regard, the efficiency of allogeneic stem cell transplantation clearly depends on the immune-mediated graft vs. leukemia effect without the risk of inducing graft-versus-host disease. Alloreactive donor NK cells generated following haematopoietic stem cell transplantation ameliorate the outcome of leukemia patients; in addition, in vivo transfer of in vitro expanded NK cells represents a crucial tool for leukemia treatment. To improve NK cell effector functions against resistant leukemia cells, novel immunotherapeutic strategies are oriented to the identification, isolation, expansion and administration of particular NK cell subsets endowed with multifunctional anti-tumor potential and tropism toward tumor sites. Moreover, the relationship between the emergence and persistence of distinct NK cell subsets during post-graft reconstitution and the maintenance of a remission state is still rather unclear.